2020
DOI: 10.3390/agriculture10030065
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Evapotranspiration of a Jujube/Cotton Intercropping System in an Arid Area Based on the Dual Crop Coefficient Method

Abstract: An accurate estimation of crop evapotranspiration (ETc) in intercropping is critical for a theoretical basis for formulating an intercropping irrigation system of fruit trees and improving the soil moisture condition of orchards in arid regions of Southern Xinjiang. Herein, observational data such as soil moisture and plant physiological indicators were measured in jujube/cotton intercropping in the Aksu region from 2015 to 2017. The evapotranspiration of single-crop jujube and cotton was estimated using the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…It is a critical innovation that will help boost the economic benefits of cotton production. The process of cotton production and development is essential for yield formation (Dong et al, 2012;Ai and Ma, 2020;Zhang et al, 2020;Wang et al, 2021). In several intercropping patterns, different intercropping patterns have little effect on the early growth and development of cotton (Sun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is a critical innovation that will help boost the economic benefits of cotton production. The process of cotton production and development is essential for yield formation (Dong et al, 2012;Ai and Ma, 2020;Zhang et al, 2020;Wang et al, 2021). In several intercropping patterns, different intercropping patterns have little effect on the early growth and development of cotton (Sun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthetic rate, intercellular CO 2 concentration, stomatal conductance, and transpiration rate are important indices of photosynthesis. Several studies have shown that intercropping improved the utilization of light energy and increased the yield per unit area in different crops ( Ai & Ma, 2020 ; Li et al, 2014 , 2020 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the dual-crop coefficient SIMDual-Kc model and the Shuttleworth-Wallace dual-source model (S-W) are two representative evapotranspiration models applicable to sparse canopy conditions in woodlands. The SIMDual-Kc model introduces a crop density coefficient Kd, and it is suitable for crops with only partial crop cover on the ground surface or high-frequency irrigation [10] (e.g., crops such as vegetables, fruit trees [11] , etc.). Also, it can achieve high accuracy with few parameters [ 12 ] [ 13 ] .…”
Section: Introductionmentioning
confidence: 99%